Penerapan Saksi Pidana Korporasi Pada Bank Dan Implikasinya - Ramelan, Yudha (UI Scholars Hub, 2018)
A criminal act by corporation is criminal offense that can be asked for criminal liability to the corporation in accordance with the laws and regulations concerning the corporation. Corporation can be punished to pay fine penalties and other additional penalties such as dissolution or revocation of business licenses. As a trust-based financial institution, if a bank commits a crime, the impact caused by the crime is not only detrimental to the bank itself, damages the reputation of the bank but also harms the community of depositors and other parties responsible for handling bank resolutions. Looking at the impact, the application of corporate criminal responsibility to banks must be carried out carefully and selectively. If these sanctions happen to a large-scale bank (systemic bank), it can be multiple effects cause.